Learning English in Mauritania : Obstacles and advantages - Ould Semane, Ghadoury (حوليات كلية الآداب والعلوم الإنسانية, 1990)
The article discusses the principal obstacles and advantages involved in learning English in Mauritania. It examines differences between linguistic and cultural systems, the unfamiliar realities encoded by vocabulary, and structural differences between English and languages familiar to Mauritanian learners. It also considers how previous language experience can create both difficulties and opportunities in the learning process.